Attachment of norovirus to histo blood group antigens: a cooperative multistep process - Mallagaray, Alvaro; Lockhauserbäumer, Julia; Hansman, Grant S.; Uetrecht, Charlotte; Peters, Thomas (Angewandte Chemie. International edition, 2015)
Human noroviruses recognize histo blood group antigens (HBGAs) as cellular attachment factors. Recently, it has been discovered that norovirus infection can be significantly enhanced by HBGA binding. Yet the attachment process and how it promotes host-cell entry is only poorly understood. The binding of a norovirus protruding (P) domain of a predominant GII.4 Saga strain to HBGAs at atomic resolution was studied. So far, independent and equivalent multiple binding sites were held responsible for attachment. Using NMR experiments we show that norovirus-HBGA binding is a cooperative multi-step process, and native mass spectrometry reveals four instead of two HBGA binding sites per P-dimer. An accompanying crystallographic study has disclosed four instead of two L-fucose binding sites per P-dimer of a related GII.10 strain1 further supporting our findings. We have uncovered a novel paradigm for norovirus-HBGA recognition that will inspire further studies into norovirus-host interactions.